Clinical cancer prevention - International Conference on Clinical Cancer Prevention St. Gallen, Switzerland 2010; Senn, Hansjèorg; Otto, Florian (Heidelberg, Germany Springer Berlin, 2011)
This book is based on presentations by some of the world?s leading experts at the Sixth International Conference on Clinical Cancer Prevention, held in St. Gallen, Switzerland, during March 2010. The main themes are the latest advances in the prevention of breast and prostate cancer and the role of infection in the development of liver and gastric cancer. Special emphasis is given to perspectives on the chemoprevention of breast cancer, as the conference included an international consensus meeting on this subject. New research findings are presented and potentially more effective cancer prevention strategies are discussed, with careful consideration of controversies. The expertise of the contributors encompasses genetics and microbiology, epidemiology, and health economics, as well as clinical cancer prevention. This book will be of interest to all who wish to learn about the most recent progress in combating the development of cancer.
Allocating Cancer-Directed Expenditures: Tensions Between Prevention, Early Detection and Treatment is Unnecessary -- Lessons Learned from Prevention Programs: Different Endpoints Should Be Used in Secondary and Tertiary Prevention -- Biomarkers for Early Detection and as Surrogate Endpoints in Cancer Prevention Trials: Issues and Opportunities -- Targeting Polyamines and Inflammation for Cancer Prevention -- Thinking About the Role (Largely Ignored) of Heavy Metals in Cancer Prevention: Hexavalent Chromium and Melanoma as a Case in Point -- Hepatitis B Virus and Cancer Prevention -- Chemoprevention of Hepatocellular Carcinoma in Chronic Hepatitis C -- Nutritional Aspects of Primary Prostate Cancer Prevention -- Prostate Cancer Prevention with 5 Alpha-Reductase Inhibitors -- Hormone Replacement Therapy and Breast Cancer -- Physical Activity and Breast Cancer: Review of the Epidemiologic Evidence and Biologic Mechanisms -- Prevention of Breast Cancer by Newer SERMs in the Future -- Chemoprevention of Hormone Receptor-Negative Breast Cancer: New Approaches Needed.
Electronic reproduction.
Keywords: Cancer -- Prevention -- Congresses; Tumors -- Prevention -- Congresses; Medicine